2014
DOI: 10.1007/s00208-014-1038-2
|View full text |Cite
|
Sign up to set email alerts
|

Global unbounded solutions of the Fujita equation in the intermediate range

Abstract: We consider the Fujita equation u t = ∆u + u p on R N with N ≥ 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…p−1 = ∞, then solutions of (1)-(2) cannot be global in time. On the other hand, the authors of[20] showed that for some u 0 (x) ∼ |x| − 2 p−1 global in time solutions of (1)-(2) exist and are unbounded as t → ∞.…”
mentioning
confidence: 99%
“…p−1 = ∞, then solutions of (1)-(2) cannot be global in time. On the other hand, the authors of[20] showed that for some u 0 (x) ∼ |x| − 2 p−1 global in time solutions of (1)-(2) exist and are unbounded as t → ∞.…”
mentioning
confidence: 99%
“…By (3.13), statement (v) applies to u 0 for each k. Sincet k → ∞, by (i) and (vi), we see that the solution u(·, ·, u 0 ) is global and Lemma 2.5 then gives the bound (3.1). Relations However, to prove the existence of such global unbounded solutions, one can use a more direct and simpler proof; see [33].…”
Section: Proof Of the Main Resultsmentioning
confidence: 99%
“…As in that paper, we take advantage of the threshold behavior of solutions which is characteristic for the range of exponents p S < p < p JL (see section 2 for details). Compared to [33], the construction here is more involved as we need to select the initial condition more carefully to guarantee that the solution u is bounded and its ω-limit set does not contain nontrivial equilibria. For the latter we will employ intersection-comparison (zero number) arguments.…”
Section: Introduction We Consider the Cauchy Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Global solutions with large-time behaviors just mentioned have mostly been known (see [21] in the case of (4) and p S < p < p JL , for example), but it is not clear whether those solutions are strong threshold solutions. On the other hand, we often use those solutions or the methods of proofs of their existence in order to prove the existence of a GSTS with the same large-time behavior.…”
Section: Introductionmentioning
confidence: 99%